Factors Associated With Pulmonary Tuberculosis Incidence In The Working Area Of Tambang Ulang Public Health Center - Nor Fadila, Desty; Rahmawati, Rahmawati; Ali As, Zulfikar; Erminawati, Erminawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Tuberculosis (TB) remains a significant public health concern in Indonesia and worldwide. It is caused by Mycobacterium tuberculosis, an acid-fast bacillus transmitted through airborne droplets. This study aimed to analyze the factors associated with the incidence of pulmonary TB in the working area of Puskesmas Tambang Ulang. An observational analytic study with a case-control design was conducted. A total of 45 respondents were selected using purposive sampling, consisting of 15 cases and 30 controls. Data were analyzed using the Chi-Square test and Odds Ratio (OR) calculations. The results showed significant associations between pulmonary TB incidence and several factors: ventilation (p = 0.002; OR = 9.333), occupancy density (p = 0.003; OR = 9.750), humidity (p = 0.003; OR = 8.000), temperature (p = 0.001; OR = 11.000), physical contact (p = 0.006; OR = 6.417), and smoking habits (p = 0.001; OR = 11.000). These findings indicate that both environmental conditions and personal behaviors contribute to the risk of TB transmission. It is recommended that communities adopt preventive behaviors such as regularly opening windows for ventilation, avoiding physical contact with TB patients, and reducing smoking habits. These efforts are expected to support health promotion strategies and serve as a basis for targeted TB prevention programs in the community.